2016
DOI: 10.2118/157426-pa
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Oilfield Aminopolycarboxylic Acids/Salts

Abstract: Summary Chelating agents are used to remove various inorganic scales, including sulfates and carbonates. They are also used as standalone stimulation fluids and as iron-control agents during acidizing treatments. The main chelating agents used in the oil field include ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), N-(hydroxyethyl)-ethylenediaminetriacetic acid (HEDTA), and glutamic acid diacetic acid (GLDA). (Note that the abbreviations for these chelating agents will be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The degree of permeability enhancement can be similar to or larger than that achieved from the injection-induced shear slip of fractures, depending on the distribution of biotite within the reservoir rocks. One concern related to this new chemical stimulation process is the thermal stability of the chelating agents 35 when a chelating agent is expected to be subjected to temperatures exceeding 200 °C during the stimulation of a reservoir of > 200 °C; however, it is not the primary target. Although we did not observe any adverse effects related to thermal stability in the present experiments at 200 °C, as expected from the reported thermal stability described in the introduction section, there is a concern that the thermal decomposition of the chelating agents and/or metal ions released due to the decomposition may generate deposits in such challenging applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of permeability enhancement can be similar to or larger than that achieved from the injection-induced shear slip of fractures, depending on the distribution of biotite within the reservoir rocks. One concern related to this new chemical stimulation process is the thermal stability of the chelating agents 35 when a chelating agent is expected to be subjected to temperatures exceeding 200 °C during the stimulation of a reservoir of > 200 °C; however, it is not the primary target. Although we did not observe any adverse effects related to thermal stability in the present experiments at 200 °C, as expected from the reported thermal stability described in the introduction section, there is a concern that the thermal decomposition of the chelating agents and/or metal ions released due to the decomposition may generate deposits in such challenging applications.…”
Section: Resultsmentioning
confidence: 99%
“…This previous study reported that GLDA is as effective as other chelating agents and has the same degree of thermal stability as HEDTA 34 . A recent study regarding the thermal stability of major chelating agents, including GLDA and HEDTA, suggested that these agents can be used at temperatures of up to approximately 200 °C 35 . These previous studies have established the potential applications of environmentally friendly chelating agents to the chemical stimulation of geothermal reservoirs, especially for reservoirs with temperatures of up to 200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the amount of nitrogen atoms that exist in the structure, chelating compounds can differ in their susceptibility to biodegradation. When compared to chelating compounds with numerous nitrogen atoms, those with a single nitrogen atom tend to be more biodegradable [107][108][109][110].…”
Section: Degradation Of Aminopolycarboxylic Acidsmentioning
confidence: 99%
“…The thermal decomposition of GLDA was studied by several authors. 20,21,[94][95][96] GLDA exhibited similar thermal stability to HEDTA when heated for 4 hours at 149 C (300 F) and 177 C (350 F) and the decomposition products were cyclic GLDA and formic acid. 20 Sokhanvarian 95 examined the decomposition of GLDA at the same temperatures and a pH of 4 up to 12 hours.…”
Section: Thermal Degradation Of Apcasmentioning
confidence: 99%
“…Calcium ions (Ca 2+ ), which are common during limestone acidizing, were also found to stabilize GLDA. 96 Resonance stabilization of free carboxylate groups is thought to provide increased thermal stability in the presence of cations and higher pH. 95,97 Hydrated sodium salts of EDTA were found to be less stable at a much lower temperature than their aqueous form.…”
Section: Apcas Degradationmentioning
confidence: 99%